Decolonizingl Special Collections: Building the Native American Literature Collection at Amherst College. - Kelly, Mike (Transactions of the American Philosophical Society, 2021)
The article presents the discussion on discourses and institutional formations undergirding the historical development and complexification of settler society. Topics include tools embedding the biases against people of color and marginalized groups characterizing other federal policies; and echo US federal policies towards Indigenous peoples showing the containment of the colonized other under the category.